Do green innovation and green competitive advantage mediate the effect of green marketing orientation on SMEs' green marketing performance? - Nuryakin Nuryakin; Tri Maryati (Cogent Business & Management, 2022)
This study attempted to fill a gap in the literature and explore the effects of green marketing orientation on SMEs green marketing performance. According to the result, the critical role of green innovation and green competitive advantage were solutions to achieving green marketing performance. The researchers implemented the moderating role of experience manager or owner and education to enhance green marketing performance. A total of 223 samples of Batik SMEs in Yogyakarta, Indonesia, were selected and investigated. The purposive sampling method helped to collect data from respondents. The results concluded that green marketing orientation significantly affected green innovation. Green marketing orientation had a significant impact on green competitive advantage. Green innovation had a significant positive effect on green marketing performance. However, the owner or manager's experiences did not moderate the relationship between green innovation and green marketing performance. The manager or owner's educational background also did not support the relationship between green innovation and green marketing performance. The result of this study indicates the mediating role of green product innovation and green product competitiveness advantage on green marketing performance.
Keywords: 650; education; experience; green competitive advantage; green innovation; Green marketing orientation; green marketing performance